PENGARUH MINUMAN ISOTONIK TERHADAP KEKASARAN PERMUKAAN EMAIL GIGI - Sari Dewiyani; Stanny Linda Paath; Wan Aisyah Darussalam (Universitas Baiturrahmah, 2022)
Introduction: One of the extrinsic factors that can cause surface enamel tooth damage occurs during consuming isotonic drinks excessively. This can lead to a demineralization process if the pH in the oral cavity reached 5,5. This study proposed to determine the effect of isotonic drinks on tooth enamel surface roughness. Method: Samples objects are 8 premolar teeth that are divided into 2 groups consisting of the treatment group and the control group. Treatment group samples were immersed in an isotonic drink and the control group was aquades of 20 ml for 5 minutes, repetition was done every 6 hours per day for a week. All samples were measured using the surface roughness tester. Results: There was an increase in the significant surface roughness of the tooth enamel after being soaked in isotonic drinks (p<0.05). Conclusion: There is an effect of isotonic drinks on the surface roughness of the tooth enamel.